The Impacts of Safety Nets in Africa : What Are We Learning? - Ralston, Laura; Andrews, Colin; Hsiao, Allan (World Bank, Washington, DC, 2017)
Safety nets in Africa are a popular policy instrument to address the widespread chronic poverty and encourage human capital investments in the education and health of children. Although there have been considerable analyses on the impacts of safety nets globally, particularly in Latin America, less been done on synthesizing results across Sub-Saharan African programs. This study fills this gap by systematically extracting and standardizing the results across impact evaluations for better understanding of what has been achieved using this policy instrument in the continent. The study finds that these programs on average have significant positive impacts on total and food consumption. The programs show promising results on asset accumulation, such as livestock ownership. However, there is substantial heterogeneity in the impacts achieved across programs for some development outcomes. Through exploring this heterogeneity in impacts, the study puts forward several suggestions for better targeting various development outcomes through modifications in the design and implementation of safety net programs.